Studi Tungku Gasifikasi dengan Penambahan Reflektor pada Burner dengan Variasi Bentuk Bulat, Segiempat dan Segitiga Terhadap Sudut Vertikal (00, 300, 450 Dan 600) - Romadlon, Shobar Bukhori Rizki; , Wijianto, ST, M.Eng.Sc (2017)
The population growth which is getting higher and higher makes the waste volume always exists and will never stop of being produced by the life. The amount will be directly proportional to the amount of population growth. Therefore, the increase in population has an impact on the increase in waste and the increase in consumption of fossil energy which its availability is getting fewer and fewer. From several technologies which have been developed to manage the biomass energy sources, one of them is through gasification method. This research used an updraft gasification furnace with the fuel of rice husk and used a variation of reflector in the burner by shapes of round, rectangle and triangle on the vertical angles (00, 300, 450, and 600). The purposes of this research are to know the burning temperature resulted from the reflector and to test the efficiency of the reflector shapes in the gasification performance. The results of the research showed that the addition of reflector in the burner influenced the fire temperature and the thermal efficiency. In the use of a round reflector, the highest temperature obtained was 728 0C and the average temperature was 626.39 0C and the effective flame was 39 minutes by the reflector with an angle of 450. In the use of a rectangle reflector, the highest temperature obtained was 762 0C and the average temperature was 653.64 0C and the effective flame was 41 minutes with a rectangle reflector of an angle of 600. The use of a triangle reflector which resulted in the highest temperature of fire was the reflector of an angle of 300 that was 771 0C and the average temperature was 612.95 0C and the effective flame was 46.5 minutes. Meanwhile, the highest efficiency in the round reflector was the reflector of angles of 00 and 600 with 16.09%. In the test of rectangle reflector, the highest efficiency was by the reflector of an angle of 00 that was 13.89%. In the triangle reflector, the highest efficiency was in the reflector of an angle of 300 with 14.73%.